2022
DOI: 10.1007/s10663-022-09533-0
|View full text |Cite
|
Sign up to set email alerts
|

Nowcasting and monitoring SDG 8

Abstract: We propose a nowcasting approach for indicators assigned to the Sustainable Development Goal (SDG) 8, calling for decent work and economic growth. The nowcasts of SDG indicators are based on dynamic factor models. In this mixed frequency framework, we exploit information from a comprehensive set of quarterly data to nowcast annually observed SDG indicators. For the model selection and specification search we evaluate the nowcast properties of the models based on a pseudo real-time data set. More recent informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Projections for the SDG targets in Austria for 2020 were presented by Bilek-Steindl and Url [13]. They showed that the SDG8 targets are strongly linked to the underlying economic situation and that the outcomes of the COVID-19 pandemic are evident in the results for 2020.…”
Section: Sustainable Development Goalsmentioning
confidence: 99%
“…Projections for the SDG targets in Austria for 2020 were presented by Bilek-Steindl and Url [13]. They showed that the SDG8 targets are strongly linked to the underlying economic situation and that the outcomes of the COVID-19 pandemic are evident in the results for 2020.…”
Section: Sustainable Development Goalsmentioning
confidence: 99%
“…In the literature, one can find empirical studies conducted based on all or selected indicators of the aforementioned goal, which were carried out for selected areas and periods using various econometric tools. Among the studies on European Union member countries (and others), one can mention an analysis of labour market inequality in the EU (Jianu et al, 2021); a partial order analysis of Eurostat SDG 8 data in the EU (Carlsen, 2021); an assessment of SDG 8 implementation in G20 countries (Lapinskaitė & Vidžiūnaitė, 2020); nowcasting and monitoring SDG 8 in Austria (Bilek-Steindl & Url, 2022).…”
Section: Literature Review and Hypothesis Development Promoting Econo...mentioning
confidence: 99%
“…The interest given to the identification of the route to be taken towards the achievement of these objectives was concentrated both at the global [25] and EU levels [26], locally-the member states [27,28]-as well as outside the EU area, the objectives being analyzed together [15], then at the objective level [29], but also only certain targets that compose various objectives [30,31].…”
Section: Introductionmentioning
confidence: 99%